A highly robust Ce3+-doped and Gd3+-mixed KLaF4 nano-glass composite scintillator. Issue 48 (29th November 2021) - Sun, Bochao; Xie, Yuqing; Zhao, Yunlong; Li, Xiang; Chen, Junfeng; Song, Yushou; Zhao, Lei; Li, Zhigang; Zhao, Hongtao; Ren, Jing; Zhang, Jianzhong
Abstract : Scintillating fibers prepared using a transparent Ce 3+ -doped nano-glass composite embedded with Gd 3+ -mixed KLaF4 nanocrystals show an excellent linear response with the irradiation dose. Abstract : Transparent Ce 3+ -doped nano-glass composites (nano-GCs) embedded with pure and Gd 3+ -mixed KLaF4 nanocrystals (NCs) are prepared by a cost-effective and reproducible glass-making and thermal treatment method. The nano-GCs can be readily cast into various sizes and shapes. The growth of the Gd 3+ -mixed NCs and the enrichment of Ce 3+ in the NCs are unambiguously revealed. Significantly enhanced emissions of Ce 3+ with a photoluminescence quantum yield as high as 92.7% are observed in the nano-GCs embedded with the Gd 3+ -mixed NCs. The integral X-ray excited emission intensity of the nano-GC is 170% that of the Bi4 Ge3 O12 (BGO) single crystal. A light output of about 853 ± 8 ph per MeV with an energy resolution of 22.27% is obtained using the nano-GC for γ-ray (662 keV) detection. The Monte Carlo simulation is carried out to understand the differences in X- and γ-ray responses. As a proof-of-concept, a real-time remote X-ray fiber dosimeter is constructed using a scintillating fiber made out of the nano-GC, which shows an excellent linear response with the irradiation dose, good thermal stability and radiation hardness.